2009
DOI: 10.1161/circoutcomes.109.862763
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology of Subtherapeutic Anticoagulation in the United States

Abstract: Background-Low international normalized ratio (INR;Յ1.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
40
0
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(42 citation statements)
references
References 38 publications
1
40
0
1
Order By: Relevance
“…Interestingly, although there are significant differences in the recommended guidelines for warfarin, healthcare systems and ethnic groups between the 2 studies, the frequency of under-dosing was similar between that study and ours. There may be common underlying causes for insufficient doses of warfarin, such as non-adherence, interruptions for procedures, recent dose reductions and second or more consecutive low INR values [13] . When warfarin is prescribed for NVAF patients, PT-INR must be maintained within the optimal range as much as possible.…”
Section: Oacs Included Warfarin and Dabigatran (An Noac) Antiplatelementioning
confidence: 99%
“…Interestingly, although there are significant differences in the recommended guidelines for warfarin, healthcare systems and ethnic groups between the 2 studies, the frequency of under-dosing was similar between that study and ours. There may be common underlying causes for insufficient doses of warfarin, such as non-adherence, interruptions for procedures, recent dose reductions and second or more consecutive low INR values [13] . When warfarin is prescribed for NVAF patients, PT-INR must be maintained within the optimal range as much as possible.…”
Section: Oacs Included Warfarin and Dabigatran (An Noac) Antiplatelementioning
confidence: 99%
“…Aux États-Unis sur 4489 patients sous AVK, sur deux ans de suivi, 34 % ont eu au moins une fois un INR inférieur à 1,5. Un patient sur cinq avec INR inférieur à 1,5 a fait un événement thromboembolique (95 % IC : 12,2-35,4 %) (Rose et al, 2009).…”
Section: Antiagrégants Plaquettaires : Mono-et Bithérapie Versus Placebounclassified
“…2 It is used for the prevention of thromboembolic complications of various disorders including atrial fibrillation, venous thromboembolism, and valvular heart disease. 3 Despite the fact that this is a highly efficacious therapy when titrated to the appropriate therapeutic range, the titration and dosing of warfarin are the most challenging and labor-intensive aspects of this therapy. There are many factors that influence its pharmacokinetics and pharmacodynamics including patient age, concurrent medications, diet, comorbidities, and genetics.…”
mentioning
confidence: 99%
“…It has been observed that low INR is addressed without a sense of urgency in the community setting, but this may be related to 2008 American College of Clinical Pharmacy guidelines that reinforce a lack of urgency in addressing low INR values, because they contain limited guidance about how to address low INR despite offering detailed instructions about how to deal with elevated INR. 3 The literature also shows that a significant proportion of patients with unstable INR values are poorly informed about the reasons for and the clinical importance of oral anticoagulation therapy for their health. Most of these patients also had insufficient knowledge of oral anticoagulation mechanism of action, the rules of treatment monitoring, and the risk of thrombotic and bleeding complications, and many of these patients stated this as the reason for poor compliance.…”
mentioning
confidence: 99%